Ten principles of residential child care - Kiaras Gharabaghi (Scottish Journal of Residential Child Care)
The history of residential care for children and young people is quite extensive and features positive stories of resilience and adult-child relationships as well as negative stories of institutional abuse and the abdication of adult responsibility (Coldrey, 2001; Sen et al., 2008). Residential child care has manifested itself in many different ways over the past century. We have accounts of orphanages in Europe, residential schools for aboriginal children in Canada and settlement homes for the children of immigrant families in the United States (Addams, 1910; Korczak, 1925; Chrisjohn & Young, 1997). Over the course of twentiethcentury history, residential child care has shifted from voluntary and often faith-based initiatives, to large institutional organisations run by medical or social work professionals, to much more community-based and often much smaller programmes staffed by professional child and youth workers (Anglin, 2002). When we think of residential child care today, we are thinking typically of professional organisations operating within a variety of public and private sectors. In Canada these can include shelters for young people who are homeless, group homes, children’s mental health centres that provide treatment for children, young people and often their families, and child welfare programmes that care for children and young people who are unable to live with their families for reasons of safety and well-being.